The Fear Domain of Iban Sebuyau, Sarawak Communities Euphemisms : Metaphor Conceptual Analysis = Domain Ketakutan Bahasa Halus Masyarakat Iban Sebuyau, Sarawak: Satu Analisis Metafora Konseptual - Clinton, Ringit; Hamidah, Abdul Wahab; Remmy, Gedat (Penerbit UTM Press, 2021)
This paper examines the use of subtle language or euphemisms in the fear domain of the Iban Sebuyau community, Sarawak. The data of this qualitative study was obtained through a field study, involving 10 Iban informants who are permanent residents in the district of Sebuyau, aged between 40-70 years. The study informants consisted of five males and five females. Structured interview method was conducted to obtain data from the fear domain, guided by questions related to the element of fear of a concrete and abstract entity. The five data analyzed in this paper are akar kayu’ (wood root), jelu sungkur (shovel animal), aki’ (grandfather), utai terebai (flying object), and bisi’ orang (the presence of people). The Conceptual Metaphor approach from the cognitive semantic framework applied in the data analysis of this study succeeded in unraveling the cognitive relationship based on the knowledge and experience of the speaker with the lexical euphemisms of Iban Sebuyau. This study provides an important contribution to the vocabulary of knowledge, in addition to explain the use of euphemisms in this domain as one of the forms of figurative language that is important and significant in the daily communication of the Iban Sebuyau community.